This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
(Adopted from Matteo De Zorzi's method.)
We substitute u = ln x to get
∫ 1 ∞ x 2 ln ln x d x = ∫ 0 ∞ e 2 u ln u 1 / e u d u = ∫ 0 ∞ e − u ln u d u
Either by seeing the similarities with the integral form of the gamma function Γ ( z ) = ∫ 0 ∞ e − t t z − 1 d t , or by noting with experience using differentiation through the integral (which often produces logarithms), we introduce a u z − 1 factor into the integral to get
∫ 0 ∞ e − u ln u d u = ∫ 0 ∞ e − u u z − 1 ln u d u ∣ ∣ ∣ ∣ z = 1 = d z d ∫ 0 ∞ e − u u z − 1 d u ∣ ∣ ∣ ∣ z = 1 = d z d Γ ( z ) ∣ ∣ ∣ ∣ z = 1 = ψ ( 1 ) Γ ( 1 ) = − γ
where ψ is the digamma function, defined as ψ = ( ln Γ ) ′ , and − ψ ( 1 ) = γ ≈ 0 . 5 7 7 2 is the Euler-Mascheroni constant.